Use of generic medicines by the Brazilian population: an evaluation of PNAUM 2014 - Bertoldi,Andréa Dâmaso (2016)
ABSTRACT OBJECTIVE To analyze the existence of differences in the use of generic medicines in Brazil according to demographic and socioeconomic variables and acquisition sources of the medicines. METHODS Population-based cross-sectional study, conducted with data from the Pesquisa Nacional de Acesso, Utilização e Promoção do Uso Racional de Medicamentos (PNAUM – National Survey on Access, Use and Promotion of Rational Use of Medicines). Data collection took place between September, 2013 and February, 2014 in homes of Brazilian cities (urban area). The use of medicines has been investigated in relation to the treatment of chronic diseases and, in the case of acute events, regarding use over the previous 15 days. Generics were identified by visualization of packaging presented by the users of the medicines. The independent variables used were sex, age, education level, economic class, and region of the Country. The statistical significance of differences between the groups was evaluated by Pearson’s Chi-squared test, considering a 5% significance level. RESULTS The prevalence of generic medicines use was 45.5% (95%CI 43.7–47.3). There was no difference considering education level. The prevalence was higher in females (47.0%; 95%CI 44.9–49.0) than in males (43.1%; 95%CI 40.5–45.8), and were higher with increasing age. Generic medicines were more used in the economic class C (47.0%; 95%CI 44.9–49.1) and in the South (50.6%; 95%CI 46.6–54.6) and Southeast (49.9%; 95%CI 46.8–53.0) regions. Generics accounted for 37.3% of the medicines provided by the Brazilian Unified Health System. CONCLUSIONS Currently, there is a choice of purchase or free provision by the Brazilian Unified Health System, characterized by quality assurance and reduced price regarding branded medicines considered as reference. In the private market, a considerable part of the population is choosing generic medicines thanks to the availability of this option for virtually all medicines most used by the population.